Zamknięci w bibliotece, czyli rozważania o metanarracjach i naukowych wizjach świata - Jędrzejko, Paweł (Er(r)go. Teoria - Literatura - Kultura, 2012)
Paweł Jędrzejko Locked in the Library: Reflections on Metanarratives and Academic Weltanschauungs The main idea underlying the article is that of the interdependence between the essential notions of the central metanarratives of logocentric cultures and the inventory of concepts available as keywords for academic research. In other words, the argument of this paper is designed to draw the attention of the reader to the fact of the interdependency between the language used to describe the world and the existence (or inconceivability of existence) of entities inhabiting it. The starting point for the musings collected here is Ludwig Wittgenstein’s famous adage, which provided the motto for the present observations. Departing from there, the argument develops into a deepened reflection concerning the limitations of the development of knowledge in a logocentric world. Eventually, it leads to the question of discourses which dictate the characteristics of everyday strategies of library and Internet research, as employed by students and scholars alike. The final part of the text is dedicated to the potential of figurative language in the search for possible solutions to the menace of the vicious circle of recognized methodologies. First and foremost, however, the present musings provide a point of departure for further philosophical and philological debate on the state of knowledge and of its development.